Factors influencing nurses' compliance with Standard Precautions in order to avoid occupational exposure to microorganisms: A focus group study - Raftopoulos Vasilios; Papastavrou Evridiki; Efstathiou Georgios; Merkouris Anastasios (BMC, 2011)
Abstract Background Nurses may acquire an infection during the provision of nursing care because of occupational exposure to microorganisms. Relevant literature reports that, compliance with Standard Precautions (a set of guidelines that can protect health care professionals from being exposed to microorganisms) is low among nurses. Additionally, high rates of exposure to microorganisms among nurses via several modes (needlesticks, hand contamination with blood, exposure to air-transmitted microorganisms) occur. The aim of the study was to study the factors that influence nurses' compliance with Standard Precaution in order to avoid occupational exposure to pathogens, by employing a qualitative research design. Method A focus group approach was used to explore the issue under study. Four focus groups (N = 30) were organised to elicit nurses' perception of the factors that influence their compliance with Standard Precautions. The Health Belief Model (HBM) was used as the theoretical framework and the data were analysed according to predetermined criteria. Results Following content analysis, factors that influence nurses' compliance emerged. Most factors could be applied to one of the main domains of the HBM: benefits, barriers, severity, susceptibility, cues to action, and self-efficacy. Conclusions Changing current behavior requires knowledge of the factors that may influence nurses' compliance with Standard Precautions. This knowledge will facilitate in the implementation of programs and preventive actions that contribute in avoiding of occupational exposure.